Age-Related Digital Divide during the COVID-19 Pandemic in China - Yu Song (MDPI AG, 2021)
China has adopted a variety of digital technologies to effectively combat the unprecedented COVID-19 pandemic. The massive utilisation of digital technologies, however, to a great extent, magnifies the age-related digital divide. This paper aims to examine the impacts of the age-related digital divide on older adults in the context of the COVID-19 pandemic. Cases of three age-related digital divide scenarios, including older people taking public transportation, seeking medical care, as well as conducting digital transactions, are collected from Chinese official news outlets. The results indicate that the COVID-19 pandemic accelerates the pace of digital technology utilisation but exacerbates the age-related digital divide. Such an age-related digital divide has largely excluded older adults from both the real society and the virtual society. Older adults’ personal attitudes and motivations, as well as education and income, governmental policies, and family and social supports, are all major contributors to the severe impacts of the age-related digital divide on old adults during the pandemic. More measures should be adopted to bridge the age-related digital divide and build a senior-friendly e-society.